The end TB strategy for India - Sachdeva, Kuldeep S; Mase, Sundari R (Indian journal of tuberculosis, 2019)
India has made great progress towards TB prevention and control with the adoption of the National Strategic Plan 2017-2025 with significantly greater allocated resources and high level political commitment. Aligning with the global End TB Strategy, India has announced the target of ending TB by 2025, five years ahead of the rest of the world. The End TB strategy is comprised of a multi-pronged approach incorporating patient-centered care and prevention, bold policies and supportive systems, and intensified research and innovation. In the past decade, India has made great strides towards ending TB, but the challenges, especially in a high burden setting, are great, and achieving our ambitious targets and goals will require partnering with all stakeholders including civil society and the community.